The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1016/j.str.2013.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Early Folding Events Protect Aggregation-Prone Regions of a β-Rich Protein

Abstract: Summary Protein folding and aggregation inevitably compete with one another. This competition is even keener for proteins with frustrated landscapes, such as those rich in β-structure. Interestingly, despite their rugged energy landscapes and high β-sheet content, intracellular lipid-binding proteins (iLBPs) appear to successfully avoid aggregation, as they are not implicated in aggregation diseases. In this study, we used a canonical iLBP, cellular retinoic acid-binding protein 1 (CRABP1), to better understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(47 citation statements)
references
References 59 publications
8
38
1
Order By: Relevance
“…These proteins are small- to medium-sized (DHFR: 159 amino acids; CRABP1: 137 amino acids; RA114: 258 amino acids) and monomeric (Figure 2). That each of these mutants is less stable than the corresponding wild type protein is demonstrated by their susceptibilities to urea denaturation for m-EcDHFR and m-RA114 (Figure S1A, B), and was reported previously for m-MmCRABP1 (Budyak et al, 2013). …”
Section: Resultssupporting
confidence: 79%
“…These proteins are small- to medium-sized (DHFR: 159 amino acids; CRABP1: 137 amino acids; RA114: 258 amino acids) and monomeric (Figure 2). That each of these mutants is less stable than the corresponding wild type protein is demonstrated by their susceptibilities to urea denaturation for m-EcDHFR and m-RA114 (Figure S1A, B), and was reported previously for m-MmCRABP1 (Budyak et al, 2013). …”
Section: Resultssupporting
confidence: 79%
“…We note in passing that the presence of well populated intermediates such as the one present in stefin-B can also lead to the exposure of aggregation-prone sequences and amyloid formation. [8][9]17,58 Here, we inferred the connection between the domain-swapping of stefin-B and its function by using the structure of its folding intermediate. However, proteins that do not populate detectable 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 23 amounts of intermediates also domain-swap 59 and such domain-swapping can also be understood using information about partially folded structural ensembles [60][61] (of which intermediate ensembles are a subset).…”
Section: Functional Residues and Folding Cooperativity Mutational Exmentioning
confidence: 99%
“…Both may be protective in cells. Additionally, recent work has suggested that the folding mechanism of CRABP1 protects aggregation-prone sequences early in the formation of native structure, providing a neat mechanism of minimizing the risk of aggregation 22 .…”
Section: Ilbps Dynamically Open To Bind Hydrophobic Substratesmentioning
confidence: 99%
“…Extensive studies of the folding and aggregation of CRABP1 have been performed 21,22,3236 . This has led to intriguing linkages: CRABP1 folds via multiple kinetic steps in which early hydrophobic collapse occurs in a few milliseconds along with formation of its helix-loop-helix motif.…”
Section: Ilbps Dynamically Open To Bind Hydrophobic Substratesmentioning
confidence: 99%
See 1 more Smart Citation